2006
DOI: 10.1109/tsp.2005.863126
|View full text |Cite
|
Sign up to set email alerts
|

Mean-square performance of a convex combination of two adaptive filters

Abstract: Abstract-Combination approaches provide an interesting way to improve adaptive filter performance. In this paper, we study the mean-square performance of a convex combination of two transversal filters. The individual filters are independently adapted using their own error signals, while the combination is adapted by means of a stochastic gradient algorithm in order to minimize the error of the overall structure. General expressions are derived that show that the method is universal with respect to the compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
354
0
24

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(389 citation statements)
references
References 19 publications
4
354
0
24
Order By: Relevance
“…According to [4], a convex combination approach is an interesting way to improve adaptive filter performance. In this case, the individual filters are independently adapted using their own error signals, while the combination is adapted by means of a stochastic gradient algorithm in order to minimize the error of the overall structure.…”
Section: Problem Formulation Let Dmentioning
confidence: 99%
See 1 more Smart Citation
“…According to [4], a convex combination approach is an interesting way to improve adaptive filter performance. In this case, the individual filters are independently adapted using their own error signals, while the combination is adapted by means of a stochastic gradient algorithm in order to minimize the error of the overall structure.…”
Section: Problem Formulation Let Dmentioning
confidence: 99%
“…As it was shown in [4], [5], when combining filters from different families, namely LMS and RLS, it is possible to take advantage of the tracking properties from each filter and obtain a structure with better performance than if each filter were implemented individually. Combinations of Kalman Filters were also proposed using different update rules as proposed in [6] and [7].…”
Section: Introductionmentioning
confidence: 99%
“…If β(t) is appropriately updated, it can be shown that the resulting model performs as well as or better than the best individual component under certain conditions [11]. The adaptation rule for β(t) is obtained as follows:…”
Section: B Convex Combinationmentioning
confidence: 99%
“…The basic idea is that two (or more) adaptive filters with complementary capabilities combine adaptively their outputs by means of a mixing parameter, in order to obtain an overall filter of improved performance. Among these schemes, convex [28][29][30], linear [31] and affine [32,33] combinations have received attention due to their simplicity and universal behavior in steady-state, i.e., the combined estimate is at least as good as the best of the component filters. And the convex combination proposed in [34] for knowledge-aided STAP obtains a significant improvement to estimate the inverse interference covariance matrix by combining the inverse of a priori known covariance matrix and a sample covariance matrix with a scale weighting parameter.…”
Section: Introductionmentioning
confidence: 99%